Japan, the sustainable society : the artisanal ethos, ordinary virtues, and everyday life in the age of limits - Lie, John (Oakland, CA : University of California Press, 2022)
"By the late twentieth century, Japan had gained worldwide attention as an economic powerhouse. Having miraculously risen from the ashes of World War II, it was seen by many as a country to be admired if not emulated. But by the early 1990s, that bubble burst in spectacular fashion. The Japanese economic miracle was over. In this book, John Lie argues that in many ways the Japan of today has the potential to be even more significant than it was four decades ago. As countries face the prospect of a world with decreasing economic growth and increasing environmental dangers, Japan offers a unique glimpse into what a viable future might look like-one in which people acknowledge the limits of the economy and environment while championing meaningful and sustainable ways of working and living. Beneath and beyond the rhetoric of growth, some Japanese are leading sustainable lives and creating a sustainable society. Though he does not prescribe a one-size-fits-all cure for the world, Lie makes the compelling case that contemporary Japanese society offers a possibility for how other nations might begin to valorize everyday life and cultivate ordinary virtues"--
From Japan as "number one" to the lost decades -- Growth reconsidered -- The regime as a concept -- Ordinary virtues -- The book of sushi -- The artisanal ethos in Japan : the larger context -- The book of bathing -- Ikigai : reasons for living.
"A Philip E. Lilienthal Book"
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 17, 2021).
eBooks on EBSCOhost
Keywords: Sustainable development -- Japan; Japan -- Economic conditions -- History; Développement durable -- Japon; Japon -- Conditions économiques -- Histoire; HISTORY / Asia / Japan; BUSINESS & ECONOMICS / Economic History; Economic history; Sustainable development; Japan; History